Modifying a commonly expressed endocytic receptor retargets nanoparticles in vivo - Sago, Cory D. (Nano Lett, 2018)
Nanoparticles are often targeted to receptors expressed on specific cells, but few receptors are (i) highly expressed on 1 cell type and (ii) involved in endocytosis. One unexplored alternative is manipulating an endocytic gene expressed on multiple cell types; an ideal gene would inhibit delivery to cell type A more than cell type B, promoting delivery to cell type B. This would require a commonly expressed endocytic gene to alter nanoparticle delivery in a cell type-dependent manner in vivo; whether this can occur is unknown. Based on its microenvironmental regulation, we hypothesized Caveolin 1 (Cav1) would exert cell type-specific effects on nanoparticle delivery. Fluorescence was not sensitive enough to investigate this question, and as a result, we designed a platform named QUANT to study nanoparticle biodistribution. QUANT is 10(8)x more sensitive than fluorescence and can be multiplexed; by measuring how 226 lipid nanoparticles (LNPs) delivered nucleic acids to multiple cell types in vivo in wildtype and Cav1 knockout mice, we found Cav1 altered delivery in a cell-type specific manner. Cav1 knockout did not alter LNP delivery to lung and kidney macrophages, but substantially reduced LNP delivery to Kupffer cells, which are liver resident macrophages. These data suggest caveolin-mediated endocytosis of nanomedicines by macrophages varies with tissue type. These results suggest manipulating receptors expressed on multiple cell types can tune drug delivery.